2019
DOI: 10.1021/acsomega.9b02083
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Exploration of Carrier Dynamics in Amorphous Pyrene–Fluorene Derivative Organic Semiconductors

Abstract: In this report, a series of amorphous organic optoelectronic pyrene–fluorene derivative materials (BP1, BP2, PFP1, PFP2, OP1, OP2) were systematically investigated through a theoretical method. Their molecular structures are different due to the difference of substitution groups at C9 of the fluorene core, which include electron-rich pyrene group (PFP1 and PFP2), relatively neutral phenyl group (BP1 and BP2), and electron-withdrawing oxadiazole group (OP1 and OP2). In the beginning, through the physical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Several experimental as well as computational studies have indicated that charge transport in crystalline molecular OS falls into a difficult regime where the charge is neither fully delocalized over the bulk material nor completely localized on a single molecule, [ 5–7 ] as had often been assumed. [ 8–11 ] We have recently shown, using advanced quantum dynamical simulations, that charge carriers in single‐crystalline OS form “flickering polarons,” objects that are half‐way between waves and particles. [ 12–14 ] We found they are delocalized over up to 10–20 molecules in the most conductive crystals and constantly change their shape and extension under the influence of the thermal motion of the atoms (crystal vibrations).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental as well as computational studies have indicated that charge transport in crystalline molecular OS falls into a difficult regime where the charge is neither fully delocalized over the bulk material nor completely localized on a single molecule, [ 5–7 ] as had often been assumed. [ 8–11 ] We have recently shown, using advanced quantum dynamical simulations, that charge carriers in single‐crystalline OS form “flickering polarons,” objects that are half‐way between waves and particles. [ 12–14 ] We found they are delocalized over up to 10–20 molecules in the most conductive crystals and constantly change their shape and extension under the influence of the thermal motion of the atoms (crystal vibrations).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the widely used theory for mobility is the Marcus theory, 25 where the two important parameters for carrier transfer are reorganization energy and a transfer integral. For OSCs, the most important is the transfer integral, which is closely correlated with the distance between the adjacent molecules.…”
Section: Resultsmentioning
confidence: 99%